Simulation Analysis of the Aerodynamic Performance of a Bionic Aircraft with Foldable Beetle Wings in Gliding Flight - Caidong Wang; Yu Ning; Xinjie Wang; Junqiu Zhang; Liangwen Wang (Applied Bionics and Biomechanics)
Beetles have excellent flight performance. Based on the four-plate mechanism theory, a novel bionic flapping aircraft with foldable beetle wings was designed. It can perform flapping, gliding, wing folding, and abduction/adduction movements with a self-locking function. In order to study the flight characteristics of beetles and improve their gliding performance, this paper used a two-way Fluid-Structure Interaction (FSI) numerical simulation method to focus on the gliding performance of the bionic flapping aircraft. The effects of elastic model, rigid and flexible wing, angle of attack, and velocity on the aerodynamic characteristics of the aircraft in gliding flight are analyzed. It was found that the elastic modulus of the flexible hinges has little effect on the aerodynamic performance of the aircraft. Both the rigid and the flexible wings have a maximum lift-to-drag ratio when the attack angle is 10°. The lift increased with the increase of the gliding speed, and it was found that the lift cannot support the gliding movement at low speeds. In order to achieve gliding, considering the weight and flight performance, the weight of the microair vehicle is controlled at about 3 g, and the gliding speed is guaranteed to be greater than 6.5 m/s. The results of this study are of great significance for the design of bionic flapping aircrafts.